Effect of spironolactone therapy on the activity of the matrix metalloproteinase system in patients with heart failure after COVID-19 - V. I. Podzolkov; A. I. Tarzimanova; A. E. Bragina; I. I. Shvedov; E. E. Bykova; А. A. Ivannikov; S. S. Khanakyan; A. M. Almyasheva (Кардиоваскулярная терапия и профилактика)
Aim. To assess the change in the activity of the matrix metalloproteinase (MMP) system after 6-month spironolactone therapy in patients with heart failure (HF) with preserved (HFpEF) and mildly reduced ejection fraction (HFmrEF) after coronavirus disease 2019 (COVID-19).Material and methods. The study included 90 patients treated at the University Clinical Hospital № 4 of the I.M. Sechenov First Moscow State Medical University with a laboratory-confirmed COVID-19. There were following inclusion criteria: age of 18-85 years; the presence of HFpEF and HFmrEF. The patients were randomized into two groups: group I (n=60) — patients with 6-month spironolactone therapy (25 mg/day) in addition to the standard therapy for HF, spironolactone was taken at a dose of 25 mg/day; Group II (comparison group, n=30) — patients who received standard therapy without spironolactone. All patients were determined plasma MMP concentrations.Results. There were no significant differences in the levels of matrix metalloproteinase-9 (MMP-9) and tissue inhibitor of metalloproteinase-1 (TIMP-1) between the groups when included in the study. A repeated investigation revealed a significant decrease in the concentrations of MMP-9 and TIMP-1 only in group I. In patients of group II, there were no significant changes in the plasma concentrations of MMP-9 and TIMP-1. The MMP-9/TIMP-1 ratio during the initial examination of patients did not have significant differences. After 6-months therapy, a significant decrease in the ratio of MMP-9/TIMP-1 was observed only in patients taking spironolactone.Conclusion. The results obtained confirm a significant decrease in MMP system activity after 6-month spironolactone therapy in patients with HFpEF and HFmrEF after COVID-19. The described antifibrotic effects of spironolactone make it possible to recommend the use of this drug in this category of patients to reduce the negative effect of MMPs on cardiovascular system.